Development of colonic stent simulator using three-dimensional printing technique: a simulator development study in Korea - Hyundam Gu; Suyoung Lee; Sol Kim; Hye-Lim Jang; Da-Woon Choi; Kyu Seok Kim; Yu Ri Shin; Dae Young Cheung; Bo-In Lee; Jin Il Kim; Han Hee Lee (Clinical Endoscopy)
Background/Aims Colonic stenting plays a vital role in the management of acute malignant colonic obstruction. The increasing use of self-expandable metal stents (SEMS) and the diverse challenges posed by colonic obstruction at various locations underscore the importance of effective training for colonic stent placement. Methods All the components of the simulator were manufactured using silicone molding techniques in conjunction with three-dimensional (3D) printing. 3D images sourced from computed tomography scans and colonoscopy images were converted into a stereolithography format. Acrylonitrile butadiene styrene copolymers have been used in fused deposition modeling to produce moldings. Results The simulator replicated the large intestine from the rectum to the cecum, mimicking the texture and shape of the human colon. It enables training for colonoscopy insertion, cecum intubation, loop reduction, and stenting within stenotic areas. Interchangeable stenotic modules for four sites (rectum, sigmoid colon, descending colon, and ascending colon) were easily assembled for training. These modules integrate tumor contours and blood vessel structures with a translucent center, allowing real-time visualization during stenting. Successful and repeatable demonstrations of stent insertion and expansion using the reusable SEMS were consistently achieved. Conclusions This innovative simulator offers a secure colonic stenting practice across various locations, potentially enhancing clinical outcomes by improving operator proficiency during actual procedures.